The use of cardio training facilities in training 7-9 year old judo athletes - Doroshenko, E. Y.; Svatyev, A. V.; Iermakov, S. S.; Jagiello, W. (Archives of Budo Science of Martial Arts and Extreme Sports, 2017)
Background & Study Aim: The experts believe that the development of a complex of modern means and methods for improving the general fitness of athletes should take into account the peculiarities of their adaptation to physical activity. The aim of this study is knowledge about effectiveness of cardio training facilities use to improve the physical and functional preparedness of judo athletes at the initial stage of training.